2021
DOI: 10.1038/s41598-021-83872-z
|View full text |Cite|
|
Sign up to set email alerts
|

Defining early changes in Alzheimer’s disease from RNA sequencing of brain regions differentially affected by pathology

Abstract: Tau pathology in Alzheimer’s disease (AD) spreads in a predictable pattern that corresponds with disease symptoms and severity. At post-mortem there are cortical regions that range from mildly to severely affected by tau pathology and neuronal loss. A comparison of the molecular signatures of these differentially affected areas within cases and between cases and controls may allow the temporal modelling of disease progression. Here we used RNA sequencing to explore differential gene expression in the mildly af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 71 publications
1
33
0
1
Order By: Relevance
“…This result corroborates a recent RNA-seq study which found that RIN affected differential gene expression analysis of AD HP tissue compared to normal HP tissue even with a RIN cut-off of 7 ( Crist et al, 2021 ). Thus, this study and others have recommended that RIN is included as a co-variate during statistical analyses ( Crist et al, 2021 ; Guennewig et al, 2021 ).…”
Section: Discussionmentioning
confidence: 98%
“…This result corroborates a recent RNA-seq study which found that RIN affected differential gene expression analysis of AD HP tissue compared to normal HP tissue even with a RIN cut-off of 7 ( Crist et al, 2021 ). Thus, this study and others have recommended that RIN is included as a co-variate during statistical analyses ( Crist et al, 2021 ; Guennewig et al, 2021 ).…”
Section: Discussionmentioning
confidence: 98%
“…However, data from the other regions, especially those that are less affected by AD such as the cerebellum, are not well-studied and are sometimes even excluded from meta-analyses [15,16]. Exploring these changes in less affected brain regions may open new avenues to enhance the molecular understanding of AD pathogenesis and may reveal key disease mechanism in affected brain regions [17]. Therefore, in this study we have combined multiple gene expression datasets from five brain regions including the hippocampus, cerebellum, frontal, entorhinal and temporal cortices of AD patients and healthy controls, and used robust rank aggregation (RRA) meta-analysis to find robust differentially expressed genes (DEGs) between AD cases and healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterised by the progressive loss of memory and neuropsychiatric symptoms, resulting from loss of cortical neurons (located in the locus coeruleus and nucleus basalis of Meynert) in the brain [ 150 , 151 ]. Several mechanisms are implicated in the pathophysiology of Alzheimer’s disease, including Aβ deposition [ 152 ], tau hyperphosphorylation [ 152 ], neuroinflammation [ 150 ], constriction of brain capillaries [ 153 ], Aβ interaction with hippocampal ghrelin/GHSR1α signalling [ 154 ], DNA damage [ 155 ], disrupted RNA hemostasias [ 156 ], mitochondrial dysfunction [ 157 ], endoplasmic reticulum (ER) stress [ 158 ], and proteostasis dysfunction [ 159 ]. The pathological hallmarks of AD [ 160 ] are deposition of extracellular Aβ plaques and intracellular neurofibrillary tangles (NFTs).…”
Section: Mechanisms Of Cell Death Induced By Dna Damage In Neurodegen...mentioning
confidence: 99%